CCNP Enterprise Wireless Design ENWLSD 300-425 and Implementation ENWLSI 300-430 official cert guide - Henry, Jerome; Hucaby, Dave (Cisco Press, 2024)
Trust the best-selling Official Cert Guide series from Cisco Press to help you learn, prepare, and practice for the CCNP Enterprise Wireless ENWLSD 300-425 and ENWLSI 300-430 exams. Well regarded for its level of detail, study plans, assessment features, and challenging review questions and exercises, CCNP Enterprise Wireless Design ENWLSD 300-425 and Implementation ENWLSI 300-430 Official Cert Guide, Second Edition, helps you master the concepts and techniques that ensure your exam success and is the only self-study resource approved by Cisco. Expert authors Jerome Henry and David Hucaby share preparation hints and test-taking tips, helping you identify areas of weakness, and improve both your conceptual knowledge and hands-on skills.